Quel accompagnement pour les personnes vulnérables en contexte de confinement ? - Malzac, P. (Ethique Sante, 2020)
What are the ethical issues in connection with the support of the most vulnerable people in a context of health crisis, forcing them to be confined? Because the concept of vulnerability is broad and complex, the “Espace éthique PACA-Corse” (PACA-Corsica Ethical Structure) has taken a particular interest in the care of children with disabilities, children entrusted to child welfare services and people with psychiatric disorders. Confinement has led to a reorganisation of the access to healthcare services and medico-social support, possibly revealing or aggravating some situations of vulnerability, or even pushing aside certain people. Those most isolated or at risk of abuse may have experienced a double confinement. How to identify and respond to the needs of people already in vulnerable situations before confinement, who, isolated in the epidemic context, have seen their vulnerabilities increase? While new ways of working have been introduced in times of containment, some were interesting, others have shown their limits. The challenge was to find the right measure to address the specificity of each situation, to activate care networks in an effective and supportive manner, despite limited resources and the emergency context. The difficulty was to make protocols and care values coexist, acting in a reactive and creative way. While revealing vulnerabilities, this period has required both humility toward uncertainty and a duty of responsibility to care for those most in need.